137 Assessment of pre-operative transoesophageal echocardiography guideline predictors of mitral valve repair success with current surgical practice. (5th June 2017) - Sall, Hanish; Ford, Lucy; Mathew, Thomas; Erhayiem, Bara
Abstract : Introduction: Mitral regurgitation (MR) is the second most common valvular heart disorder and severe MR brings with it a poorer prognosis. Successful mitral valve (MV) repair for prolapse has similar patient survival compared with expected outcomes. Precise definition of MV morphology is required to determine the complexity and feasibility of MV repair. Several echocardiographic parameters in international guidelines try and identify patients at risk of treatment failure. These are largely based on one study in 2002 where quadrangular resection and sliding plasty was the surgical technique of choice for the majority of MV prolapse. More modern surgical practice largely spares resection of valve tissue and employs neo-chordae/transfer techniques. This brings into question the applicability of previous imaging predictors for procedural success. Hypothesis: Are echocardiographic parameters in current recommendations accurate in predicting successful mitral valve repair? Methods: A retrospective study was carried out on all MV repairs undertaken at Nottingham University Hospitals NHS Trust between August 2015 and August 2016. Significant residual MR was defined as moderate or above. Echocardiographic predictors of suitability were taken from the European Association of Cardiovascular Imaging 2013 guidelines. Inclusion criteria: Pre-operative transoesophageal echocardiogram (TOE); post-operative baseline transthoracic echocardiogram (TTE) at 3–6 months. Exclusion criteria: lack of pre-op TOE or post-op TTE; previous cardiac surgery. Results: 52 patients underwent MV repair. Of these, 28 patients had complete imaging as set out by the inclusion criteria. Data presented as mean±SD unless otherwise stated. 4/28 (14%) patients had significant residual MR. Table 1 shows demographics, pre-operative chamber characteristics, MV characteristics, operative technique and post-op MR characteristics between the two groups. There were no significant differences in demographics, cardiac chambers, MV or operative characteristics between patients with no significant residual MR and significant residual MR groups. No patients had quadrangular resection. The clinical characteristics of the 4 patients with significant residual MR are presented in table 2. Discussion: In this small, single-centre, retrospective study, we found that none of the current echocardiographic predictors of suitability for MV repair were associated with presence of residual significant MR. Further prospective work is required to re-evaluate clinical and imaging data in predicting MV repair success with current surgical practice and improved imaging techniques.